2020
DOI: 10.1183/23120541.00317-2020
|View full text |Cite
|
Sign up to set email alerts
|

European Respiratory Society International Congress, Madrid, 2019: nontuberculous mycobacterial pulmonary disease highlights

Abstract: Once overlooked, awareness of nontuberculous mycobacterial pulmonary disease (NTM-PD) is rapidly rising, in line with increasing prevalence worldwide. The European Respiratory Society (ERS) International Congress 2019, held in Madrid, Spain, provided a platform for invigorating discussions and exciting new research in the field. This article explores approaches being taken to combat NTM-PD with a focus not only on novel prevalence and risk factor data, but also on emerging antimicrobials and their routes of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(65 reference statements)
0
3
1
Order By: Relevance
“…In contrast to other studies that have identified MAC as the dominant NTM species [34,35], our study did not isolate any MAC species from the specimens. Instead, we observed a prevalence of species such as M. abscessus, M. chelonae, M. fortuitum, M. mucogenicum, M. gordonae, M. kansasii, and M. simiae in East Azerbaijan, Iran.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies that have identified MAC as the dominant NTM species [34,35], our study did not isolate any MAC species from the specimens. Instead, we observed a prevalence of species such as M. abscessus, M. chelonae, M. fortuitum, M. mucogenicum, M. gordonae, M. kansasii, and M. simiae in East Azerbaijan, Iran.…”
Section: Discussioncontrasting
confidence: 99%
“…A Phase II proof-of-concept study of inhaled NO in patients with NTM-PD has also been completed (trial registration: NCT03748992) and an open-label study of the at-home NO generator LungFit® GO is currently taking place (trial registration: NCT04685720). In vitro studies have shown potent antibacterial activity against M. abscessus following perfusion with NO in combination with clofazimine and amikacin [ 100 ]. Further studies are needed to assess the efficacy of NO against M. abscessus infection as part of combination therapy, and also its ability to reach bacteria sequestered in biofilms and macrophages.…”
Section: Methodsmentioning
confidence: 99%
“…SGM include Mycobacterium avium complex (MAC), Mycobacterium chimaera , Mycobacterium kansasii , Mycobacterium malmoense , and Mycobacterium xenopi , whereas RGM comprise species from the Mycobacterium abscessus and Mycobacterium fortuitum complexes ( Alffenaar et al , 2021 ). In human infections, identifying NTM is crucial for determining clinically relevant species and the best treatment plan ( Chalmers et al , 2019 ; Mwangi et al , 2022a ).…”
Section: Introductionmentioning
confidence: 99%